التدريس الإلكتروني الجامعي عن بعد في ظل وباء كوفيد 19 (معهد علوم وتقنيات النشاطات البدنية والرياضية جامعة باتنة2 انموذجا) - هدوش, عيسى; معلم, عبد المالك; ناصري, محمد (جامعة الوادي - University of Eloued, 2021)
يهدف البحث إلى التعرف صعوبات التحول من التدريس الكلاسيكي الى التدريس عن بعد التي تواجه الطلبة من حيث جودة الدروس والمرافقة البداغوجية من طرف الاساتذة للموسم الجامعي2020 .وقد استخدم الباحث المنهج الوصفي لملائمته لطبيعة البحث، فيما تكونت عينة البحث من 85 طالب من معهد علوم وتقنيات النشاطات البدنية والرياضية باتنة 2 . طبق على هذه العينة استبيان الكتروني ، وتم معالجة البيانات إحصائيا باستخدام الحقيبة الاحصائية SPSS. من اهم النتائج المتحصل عليها ان معظم الطلبة يشتكون من عدم مرافقة الاساتذة في العملية التعليمية بينما ظلت جودة الدروس تتسم بالعموم ، وقد اوصى الباحث بضرورة تخصيص اوقات معينة للتواصل المباشر مع اساتذ المادة والطلبة فيما بينهم لتعميق الفهم والاستفادة ، والتكفل بالطالب من الناحية البيداغوجية . Abstract: The research aims to identify the difficulties of switching from classical teaching to distance teaching facing students in terms of the quality of the lessons and the pedagogical accompaniment of the professors for the 2020 academic year. The researcher used the descriptive method to suit the nature of the research, while the research sample consisted of 85 students from the Institute of Science and Technology Activities Physical and sports Batna 2. An electronic questionnaire was applied to this sample, and the data were processed statistically using SPSS. One of the most important results obtained is that most students complain about the lack of accompanying teachers in the educational process, while the quality of the lessons remained general, and the researcher recommended that certain times should be allocated for direct communication with the subject teachers and students among themselves to deepen understanding and benefit, and to take care of the student from the pedagogical aspect
Online university distance learning in Covid 19 epidemic (Institute of Sciences and Techniques of Physical and Sports Activities, University of Batna 2 as a model)
مقال
Keywords: التدريس، التدريس الالكتروني ، التدريس الالكتروني عن بعد، كوفيد 19; Teaching, e-.and benefit, and to take care of the student from the pedagogical aspect teaching, distancee-learning, COVID-19